Strategi Pemberdayaan Masyarakat dalam Pengelolaan Sampah Plastik pada Program Zero Waste Tour - Fanes Ardhito Veriyanto; Susi Hardjati (Community Engagement and Emergence Journal (CEEJ), 2026)
The purpose of this study is to identify and analyze community empowerment strategies in plastic waste management in the zero waste tour program by the ECOTON Gresik community. The research method used is a qualitative method with a case study approach. The data collection techniques in this study consist of three techniques, namely observation, interviews, and documentation. The analysis techniques used were data reduction, data display, and conclusion and verification. The results of the study show that community empowerment strategies in plastic waste management in the Zero Waste Tour Program by the ECOTON Gresik community have been realized in a tangible and comprehensive manner through an approach that emphasizes motivation, awareness raising and skills training, self-management, and network building and development. This program not only increases public knowledge about the dangers of plastic waste to the environment, especially rivers and ecosystems, but also successfully shapes new attitudes and behaviors that are more responsible in reducing, sorting, and managing plastic waste. The community is no longer positioned as objects, but as active subjects of change involved in every stage of the activities, from planning and implementation to evaluation. This involvement is strengthened through direct practice, continuous mentoring, and cross-sector network support that expands the program's reach and legitimacy.